A comparison between various polymeric membranes for oily wastewater treatment via membrane distillation process - Suriani Abu Bakar (Tanjung Malim, 2023)
A comparison between various polymeric membranes for oily wastewater treatment via membrane distillation process by Suriani Abu Bakar